Metamorphism and deformation of mafic and felsic rocks in Bhavani Shear Zone, Tamilnadu, India - Prian, Raja K; Singh, Kuldeep; Kumar, M. Vinoth; Kumar, R. S. (International Journal of Advanced Geosciences, 2014)
In southern India, Nilgiri block (NB) is separated from Western Dharwar Craton (WDC) and Palghat Cauvery Shear Zone (PCSZ) by Moyar and Bhavani shear zone (MSZ and BSZ) respectively. The Archaean high grade Bhavani shear is composed predominantly of meta-gabbro, meta-anorthosite and garnetiferrous gabbro, along with pyroxenite and amphibolites. The mafic rocks associated with hornblende gabbro and pyroxenite, retain magmatic structures and show evidence of major change in grain size and shapes granofelses of igneous relicts. The BSZ and MSZ are steeply-dipping thrusts, the Moyar shear in predominantly dip-slip transport. Gabbro majorly consists, assemblage of almandine-pyrope garnet and augite clinopyroxene as phenocryst with coexisting porphyroblasts texture. Geological structure relations combined with petrographical analysis from Moyar Bhavani shear zone (MBSZ) suggest that the gabbroic metamorphism was related to formation of the shear zone. Intermingled gabbroic rocks escaped metamorphism because they remained magmatic to lower temperatures, and experienced shorter and lower temperature sub-solidus cooling intervals. The felsic rocks underwent relatively high temperature solid-state deformation, as indicated by gabbro replacing K-felspar and subgrain patterns in quartz. The felsic rocks were deformed in the solid state because of their high proportion of relatively weak minerals (quartz and biotite), whereas, the mafic rocks mostly escaped sub-solidus deformation, except in local high-strain zone of their high proportion of relatively (hornblende and plagioclase) strong minerals. Keywords: Amphibolite; Anorthosite; Bhavani Shear Zone; Pyroxenite; Garnet and Gabbro.